2020
DOI: 10.3390/cancers12082325
|View full text |Cite
|
Sign up to set email alerts
|

Sex Hormones and Hormone Therapy during COVID-19 Pandemic: Implications for Patients with Cancer

Abstract: The novel coronavirus disease 2019 (COVID-19) shows a wide spectrum of clinical presentations, severity, and fatality rates. The reason older patients and males show increased risk of severe disease and death remains uncertain. Sex hormones, such as estradiol, progesterone, and testosterone, might be implicated in the age-dependent and sex-specific severity of COVID-19. High testosterone levels could upregulate transmembrane serine protease 2 (TMPRSS2), facilitating the entry of severe acute respiratory syndro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
102
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(111 citation statements)
references
References 90 publications
1
102
0
2
Order By: Relevance
“…In the present study, differences in mortality due to COVID-19 between the sexes were not identified, as reported in other studies [9 , 11 , 19] . Sex hormones are believed to be important in the immune response; estrogen is known to act as an immune booster, but androgens need to be further investigated for their interaction with COVID-19 [38 , 39] .…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, differences in mortality due to COVID-19 between the sexes were not identified, as reported in other studies [9 , 11 , 19] . Sex hormones are believed to be important in the immune response; estrogen is known to act as an immune booster, but androgens need to be further investigated for their interaction with COVID-19 [38 , 39] .…”
Section: Discussionmentioning
confidence: 99%
“…Evidences suggest that male gender and aged persons are key factors connected to higher danger of severe events and death from COVID-19[ 36 , 37 ]. The enhancing mortality rate from COVID-19 for males (2.4 times) than for females is overall comparable to that originated in other coronaviruses during the past two years, including the SARS-CoV and the MERS-CoV[ 37 - 39 ].…”
Section: Discussionmentioning
confidence: 99%
“…Variations in weight, body mass index, and hormonal changes (during puberty, menstrual cycles, and menopause) can be factors that lead to sexual differences in adverse reactions to antiviral drugs [81] Hence, an appropriate treatment for patients is the use of hormone therapy. Sex hormones such as testosterone, progesterone, and estradiol can be considered in these therapeutic processes ( Table 1 ) [80] , [82] , [83] .…”
Section: Pharmacotherapy Of the Cov-linked Syndromesmentioning
confidence: 99%